2017
DOI: 10.4306/pi.2017.14.6.894
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with the Fear of Falling in Community-Living Elderly People in Korea: Role of Psychological Factors

Abstract: Little is known about the risk factors for the fear of falling in elderly Korean individuals. Thus, the present study aimed to investigate the risk factors for fear of falling in a representative elderly population of over 10,000 individuals aged 65 years and older. A multivariate multinomial analysis revealed that the risk factors associated with a severe fear of falling were being female [odds ratio (OR)=4.396], older age (OR=5.550 for those aged ≥85 years), lower level of education (OR=0.719 for those with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 10 publications
5
29
0
5
Order By: Relevance
“…1 The fall frequency of individuals aged 65 or over has been found to range from 21.2% to 39.7% in different regions of the world. [20][21][22][23] Six-month falls incidence in Sweden was found to be 19.9%, 20.0% and 32.1% for individuals over 60, 80 and 90 years of age, respectively. 15 A study in the United States found that 50% of people aged 80 and over fall at least once each year.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…1 The fall frequency of individuals aged 65 or over has been found to range from 21.2% to 39.7% in different regions of the world. [20][21][22][23] Six-month falls incidence in Sweden was found to be 19.9%, 20.0% and 32.1% for individuals over 60, 80 and 90 years of age, respectively. 15 A study in the United States found that 50% of people aged 80 and over fall at least once each year.…”
Section: Discussionmentioning
confidence: 97%
“…According to the WHO Global Report, 28%‐35% of people aged 65 and over fall each year, and this rate increases to 32%‐42% for those over 70 years of age . The fall frequency of individuals aged 65 or over has been found to range from 21.2% to 39.7% in different regions of the world . Six‐month falls incidence in Sweden was found to be 19.9%, 20.0% and 32.1% for individuals over 60, 80 and 90 years of age, respectively .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations